2020
DOI: 10.1016/j.omtm.2020.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Organoids: A Human Model for AAV Capsid Selection and Therapeutic Transgene Efficacy in the Brain

Abstract: The development of gene therapies for central nervous system disorders is challenging because it is difficult to translate preclinical data from current in vitro and in vivo models to the clinic. Therefore, we developed induced pluripotent stem cell (iPSC)-derived cerebral organoids as a model for recombinant adeno-associated virus (rAAV) capsid selection and for testing efficacy of AAV-based gene therapy in a human context. Cerebral organoids are physiological 3D structures that better recapitulate the human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 43 publications
(54 reference statements)
0
26
0
Order By: Relevance
“…This is an important observation, as it demonstrates findings seen in organoids may recapitulate what would be seen in adult human tissue. Studies have also used human iPSC-derived cerebral organoids to study AAV transduction ( Latour et al, 2019 ; Depla et al, 2020 ). However, these studies only looked at neuronal transgene expression achieved from the AAV vectors used.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important observation, as it demonstrates findings seen in organoids may recapitulate what would be seen in adult human tissue. Studies have also used human iPSC-derived cerebral organoids to study AAV transduction ( Latour et al, 2019 ; Depla et al, 2020 ). However, these studies only looked at neuronal transgene expression achieved from the AAV vectors used.…”
Section: Discussionmentioning
confidence: 99%
“…The transduction properties of two commonly used AAV serotypes (AAV5 and 9) were compared for transgene expression at the mRNA and protein levels, together with the presence of viral DNA. This study reported a higher transduction of the AAV5 compared to AAV9, in organoids and neural cells (Depla et al, 2020). This work set the ground for the use of iPSCs-derived human organoids as valid system for testing AAV properties and will be likely a valuable platform for holistic characterization of AAV properties in vitro and identification of the best therapeutic candidates.…”
Section: Ipscs As a Model For Aav-based Gene Therapy Testingmentioning
confidence: 63%
“…Capsid variant AAV9-NVVRSSS was selected based on a high transduction efficiency in AAV library screens in human cells focusing on the NXXRXXX peptide motif (Börner et al, 2020) (Weinmann et al, unpublished data). By contrast, wildtype AAV2 and AAV9 serotypes poorly transduce human iPSC-derived neurons (Depla et al, 2020; Duong et al, 2019) (Weinmann et al, unpublished data). Cocultures of induced human neurons and primary rat astrocytes in 96-well plates were transduced with AAV vectors encoding an enhanced GFP reporter driven by the ubiquitously active cytomegalovirus promotor at day 21 of maturation.…”
Section: Methodsmentioning
confidence: 99%
“…Screening of AAV capsid variants in different human primary cell types already pointed to peptide motifs resulting in enhanced transduction rates of specific cell types (Börner et al, 2020; Westhaus et al, 2020). Human neurons differentiated from induced human pluripotent stem cells (iPSC) are increasingly used as a test system for AAV vectors designated for gene therapy of neurological disorders (Depla et al, 2020; Duong et al, 2019). Neuronal differentiation of human iPSC by small molecules however, is a lengthy procedure and leads to a heterogeneous mixture of various neuron types and non-neuronal cells (Strano et al, 2020; Yao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%